2018
DOI: 10.1007/s00167-018-5196-8
|View full text |Cite
|
Sign up to set email alerts
|

A small difference in recovery between total knee arthroplasty with and without tourniquet use the first 3 months after surgery: a randomized controlled study

Abstract: PurposeWhen a tourniquet is used during surgery on the extremities, the pressure applied to the muscles, nerves and blood vessels can cause neuromuscular damage that contributes to postoperative weakness. The hypothesis was that the rehabilitation-related results would be improved if total knee arthroplasty (TKA) is performed without the use of a tourniquet.Methods81 patients with osteoarthritis of the knee who underwent TKA surgery were randomized to surgery with or without tourniquet. Active flexion and exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 42 publications
2
59
0
3
Order By: Relevance
“…Tourniquets can reduce blood loss during operations and provide a better view for surgeons, but the use of a tourniquet may be related to muscle damage, paralysis, severe thigh pain, delayed rehabilitation, and reduced patient satisfaction [12, 13]. Considering these concerns, not using a tourniquet during TKA surgery can avoid those side effects and promote recovery postoperatively.…”
Section: Introductionmentioning
confidence: 99%
“…Tourniquets can reduce blood loss during operations and provide a better view for surgeons, but the use of a tourniquet may be related to muscle damage, paralysis, severe thigh pain, delayed rehabilitation, and reduced patient satisfaction [12, 13]. Considering these concerns, not using a tourniquet during TKA surgery can avoid those side effects and promote recovery postoperatively.…”
Section: Introductionmentioning
confidence: 99%
“…Tourniquet can reduce intraoperative bleeding and facilitate bone-prosthesis adhesion, but increase the amount of HBL after operation [37]. Some studies have also shown that tourniquet increases the degree of pain in a short time after surgery, but does not increase the recovery time of knee function after TKA [38]. Under the principle of ERAS, it has been controversial whether to use tourniquet during operative.…”
Section: Discussionmentioning
confidence: 99%
“…In ankle arthroscopy, there were only a few researches focusing on this issue. Zaidi et al conducted a prospective nonrandomized study to explore the effects of tourniquet use in ankle arthroscopy, they noted that tourniquet use showed no clinical disadvantages in regard to duration of operation, maximum intraoperative uid pressures or visibility, and announced ankle arthroscopy was possible without the use of a tourniquet [22]. Dimnjakovic et al also found that in ation of a tourniquet did not result in increased duration of operation, maximum intraoperative uid pressures or visibility after anterior ankle arthroscopy [8].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of tourniquet on the amount of limb swelling has been investigated by many authors [22][23].…”
Section: Discussionmentioning
confidence: 99%